ChatGPT - Baker, Pamela, 1957- (--For dummies., 2023)
ChatGPT For Dummies demystifies the artificial intelligence tool that can answer questions, write essays, and generate just about any kind of text it's asked for. This powerful example of generative AI is widely predicted to upend education and business. In this book, you'll learn how ChatGPT works and how you can operate it in a way that yields satisfactory results. You'll also explore the ethics of using AI-generated content for various purposes. Written by a journalist who's been on the front lines of artificial intelligence for over a decade, this book dives deep into ChatGPT's potential, so you can make informed decisions--without asking ChatGPT for help.